Bridge Pile Response to Lateral Soil Movement Induced by Installation of Controlled Modulus Columns. (2016) - Nguyen, Huu Hung; Khabbaz, Hadi; Fatahi, Behzad; Kelly, Richard
Abstract: Controlled modulus columns (CMC) for ground improvement are installed using a hollow stem displacement auger to induce lateral soil displacement effect, followed by grout injection. While the method reduces spoils, the excessive lateral soil displacement may damage adjacent structures. Although there has been growing interest in quantifying such effects, only a handful of studies have been attempted. This paper presents the results of a numerical investigation on the CMC installation effect on an existing bridge pile using the three-dimensional finite difference software package FLAC 3D . It has been found that when the CMC is long and the existing bridge pile is slender, the pile bending moment and pile lateral movement, induced by the CMC installation effect, can be significant.